PENGARUH DANA BAGI HASIL (DBH), DANA ALOKASI UMUM (DAU) DAN DANA ALOKASI KHUSUS (DAK) TERHADAP BELANJA MODAL PEMERINTAH DAERAH KABUPATEN/KOTA DI JAWA BARAT - Dimas Ariyawan Santoso; Maya Widyana Dewi; Sri Laksmi Pardanawati (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
This study aims to examine the influence of revenue sharing funds, general allocation funds, and special allocation funds on capital expenditures of Regency/City Governments in West Java. This study uses secondary data in the form of quantitative data contained in regional financial statistics reports from APBD and TKDD reports. Data collection techniques are obtained through documentation and literature studies. The population in this study was 27 Regencies/Cities in West Java, with a sample size of 135 taken using the purposive sampling method. The data analysis method used is descriptive statistics, classical assumption tests in the form of normality tests, multicollinearity, autocorrelation, heteroscedasticity, and hypothesis testing in the form of multiple linear regression analysis, F test, t test, and R2 test. The results of the study indicate that Revenue Sharing Funds have a positive effect on Capital Expenditures with a significance value of 0.003 < 0.05 and a t count value of 3.041 > 1.65648 t table. General Allocation Fund has a positive effect on Capital Expenditure with a significance value of 0.000 < 0.05 and a t count value of 4.330 > 1.65648 t table. While the Special Allocation Fund has no effect on Capital Expenditure with a significance value of 0.743 > 0.05 and a t count value of 0.329 < 1.65648 t table.